Answer:
When 6x - 4 = 8, x = 2.
Step-by-step explanation:
6x - 4 = 8
Add 4 to both sides.
6x = 12
Divide both sides by 6.
x = 2
Proof:
6x - 4 = 8
Substitute variable.
6(2) - 4 = 8
Multiply 6 and 2.
12 - 4 = 8
Subtract 4 from 12.
8 = 8
G(x) would have to be -->7 units.
The relationship between f(x) and s(x) where s(x)=af(x-b)+z is that g(x) is f(x) stretched by the reciprocal of a, b is the liar (all x values go up if b goes down and visa versa), and it moves up z units.
Answer:
Go to the search bar and type up photos. Press on the photo/screenshot you want and it should give you a button you can use to crop.
Step-by-step explanation:
(2,-1) The intersecting point is the point where the two lines meet.
Answer:
24
Step-by-step explanation: